Hak Mendapatkan Pendidikan Tinjauan Epistimologi dan Aksiologi Filsafat Pendidikan Islam - Samsul Hadi (LP2M STIT Palapa Nusantara, 2017)
Education as one of the key progress and development of a country, Therefore, the right to get education for the community and citizens, of course now must be acceptable for all layers and the community. This review, will speak on the